L’étude des matériaux organiques dans les tombes du haut Moyen Âge (France, Suisse et Allemagne occidentale) : un apport majeur à la connaissance des pratiques funéraires et du vêtement - Florence Carré; Antoinette Rast-Eicher; Bruno Bell; Julien Boisson (Archéologie Médiévale)
The usefulness of fragments of organic material preserved in the environment of metallic objects in a funerary context has been widely demonstrated in Switzerland and Germany. Their detailed study provides valuable information on practices, clothing and sepulchral deposits. This kind of approach is rarely observed in France. Some of the methods have been tested on a few graves of an important cemetery discovered in Harfleur (Seine-Maritime). This article offers a historiographical overview of the topic in question, a critical review of sampling techniques, global facts on organic materials conservation, the method of extraction and recording, as well as comments on the difficulties of identification or interpretation. The issue of renditions is also discussed. Many examples and four case studies illustrate the results.